Behavioural adaptation of Malay families and housing modification of terrace houses in Malaysia - Abdul Rahim, Zaiton; Hashim, Ahmad Hariza (Centre for Environment-Behaviour Studies (cE-Bs) and University Publication Centre (UPENA), UiTM, 2012)
This paper examines the behavioural adaptation of Malay families living in terrace houses in relation to the activity system, privacy and social interaction and terrace housing modification due to the constraint of terrace housing designs. The study uses case studies of 11 Malay families living in the three-bedroom two-storey terrace houses in two urban locations in Malaysia. Findings indicate that behavioural adaptation resulted in changes in some aspects of the Malay culture and housing modifications provided a more supportive living environment but have adverse effects on individual family and housing community due to the constraints of the terrace housing design.